APLIKASI ANALISIS SHIFT SHARE DAN LOCATION QUOTIENT SEKTOR PEREKONOMIAN DI KECAMATAN DELANGGU KABUPATEN KLATEN - Barokah, Umi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2006)
Various of economic sector in Delanggu sub district, Klaten Regency by Shift share and Location Quotient Analyze Approach. This research aim to identify sector becoming base in Delanggu sub district, economic sector that becoming priority sector. Used method is descriptive method with Shift Share. Data used including Regional Domestic Product Bruto data of Delanggu sub district and Klaten 200-2004, Klaten in Number 2000-2004